Current State and Perspectives of Ferrous Metallurgy Development in Russia - Tsvetkov, Konstantin; Slepov, Vladimir; Sekerin, Vladimir; Gorokhova, Anna; Skubriy, Evgeniy (International Journal of Engineering and Technology, 2018)
The current state of ferrous metalsâ€™ market is characterized by intensive development; the metallurgical production in several Asian countries has taken the leading position in the world; and metallurgy in the USA, Germany and Russia faces strong pressure from manufacturers of metals in Asian countries. The metallurgical complex in Russia is experiencing the period of its reconstruction: the time-consuming open-hearth steelmaking has been virtually deleted in the country, electrometallurgy is developing slowly, especially production of steel in induction furnaces, the amount of rejects in rolling is significant, and production of rolled products is still insufficient.The key changes in metallurgy are observed in rolling production. High quality finishing of metal allows to reduce the overall amount of rejects in metallurgical production, improve the interest of the market in the produced metal, and increase the export potential of the Russian metallurgy.The reduced production in the engineering industry after 1990 had the most negative impact on the development of Russian ferrous metallurgy. An important element that contributes to improving the economic efficiency through the activity of the metallurgical complex is more uniform placement of production across the country, particularly development of metallurgy in the Far East Federal District.Â Â Â